Relation Between Coronary Tortuosity and Vasomotor Dysfunction in Patients Without Obstructed Coronaries? - Jansen, Tijn P. J.; van Keeken, Kyra; Konst, Regina E.; Dimitriu-Leen, Aukelien; Maas, Angela H. E. M.; van Royen, Niels; Damman, Peter; Elias-Smale, Suzette (Frontiers in Cardiovascular Medicine, 2022)
Background: A large proportion of patients with angina and no obstructive coronary artery disease (ANOCA) has underlying coronary vasomotor dysfunction (CVDys), which can be diagnosed by a coronary function test (CFT). Coronary tortuosity is a common angiographic finding during the CFT. Yet, no data exist on the association between vasomotor dysfunction and coronary tortuosity. Aim: To investigate the association between CVDys and coronary tortuosity in patients with ANOCA Methods: All consecutive ANOCA patients who underwent clinically indicated CFT between February 2019 and November 2020 were included. CFT included acetylcholine spasm testing to diagnose epicardial or microvascular spasm, and adenosine testing to diagnose microvascular dysfunction (MVD). MVD was defined as an index of microvascular resistance (IMR) ≥ 25 and/or coronary flow reserve (CFR) <2.0. Coronary tortuosity, was scored (no, mild, moderate or severe) based on the angles of the curvatures in the left anterior descending (LAD) artery on angiography. Results: In total, 228 patients were included (86% female, mean age 56 ± 9 years). We found coronary artery spasm in 81% of patients and MVD in 45% of patients (15%: abnormal CFR, 30%: abnormal IMR). There were 73 patients with no tortuosity, 114 with mild tortuosity, 41 with moderate tortuosity, and no patients with severe tortuosity. No differences were found in cardiovascular risk factors or medical history, and the prevalence of CVDys did not differ between the no tortuosity, mild tortuosity and moderate tortuosity group (82, 82, and 85%, respectively). Conclusion: In this study, CVDys was not associated with coronary tortuosity. Future experimental and clinical studies on the complex interplay between coronary tortuosity, wall shear stress, endothelial dysfunction and coronary flow are warranted.